Heat-resistant flame-retardant impact-resistant CPVC cable protection pipe and preparation method thereof

CN122992553APending Publication Date: 2026-10-27SUZHOU BAONIU PIPE IND CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611125231.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]CPVC管材的技术矛盾主要在于:提高耐热性通常需要提高CPVC含量、加入刚性无机相或提高体系玻璃化温度,但这些措施容易提高熔体黏度并降低冲击韧性;提高抗冲击性通常需要加入橡胶相、增塑剂或韧性改性剂,但这些组分又可能降低维卡软化温度、热变形稳定性和阻燃性

Benefits of technology

1.本发明通过外层中ACR抗冲改性剂和聚酯型增塑剂主要分布于管壁外侧,能够吸收落锤冲击能量,减少外冲击开裂,同时避免韧化组分在整个管壁中过量分散而降低整体耐热性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992553A_ABST
    Figure CN122992553A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer pipes, and particularly relates to a heat-resistant, flame-retardant and impact-resistant CPVC cable protection pipe and a preparation method thereof; aiming at the contradiction between heat resistance and flame retardation of the current CPVC cable protection pipe; the application is constructed in a three-layer composite structure, and the inner layer, the gradient transition layer and the outer layer are arranged from inside to outside; the outer layer material is composed of CPVC resin, ACR modifier, polyester plasticizer, organic tin stabilizer and lubricant; the inner layer material is composed of CPVC resin, modified nano-SiO2, organic tin stabilizer, ACR processing aid and lubricant; the gradient transition layer is formed by mixing the inner layer material and the outer layer material in a gradient ratio, and adding maleic anhydride grafted chlorinated polyolefin as an interfacial compatibilizer; wherein, silicon carbide whiskers treated by a coupling agent are added in the inner layer, and elastomer microspheres treated by surface treatment are added in the outer layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer pipe technology, specifically relating to a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe and its preparation method. Background Technology

[0002] Chlorinated polyvinyl chloride, or CPVC for short, is a thermoplastic resin obtained by post-chlorination of PVC. Compared with ordinary PVC, CPVC typically has higher heat resistance, flame retardancy, and chemical resistance, making it suitable for applications such as pipes, fire sprinkler pipes, and industrial pipelines. CPVC has a higher Vicat softening temperature than traditional PVC and is self-extinguishing, thus it is widely used in fields requiring heat resistance, flame retardancy, and insulation, such as cable protection pipes.

[0003] Publication number CN103012998A discloses a chlorinated polyvinyl chloride (CPVC) pipe for cable protection. Its components include CPVC resin, PVC resin, heat-resistant modifier NR-188, calcium-zinc stabilizer, filler, chlorinated polyethylene, paraffin wax, stearic acid, and pigment, and it is extruded using a standard CPVC pipe production line. This solution aims to improve Vicat softening temperature and heat dissipation while ensuring impact resistance and toughness. However, this solution is still a single-layer blend formulation and does not resolve the structural contradiction between the outer toughening component reducing overall heat resistance and the inner rigid filler reducing overall impact resistance.

[0004] The main technical challenges of CPVC pipes lie in the following: improving heat resistance typically requires increasing the CPVC content, adding a rigid inorganic phase, or raising the glass transition temperature of the system; however, these measures tend to increase melt viscosity and reduce impact toughness. Improving impact resistance usually requires adding a rubber phase, plasticizers, or toughening modifiers; however, these components may reduce the Vicat softening temperature, heat distortion stability, and flame retardancy. Existing publicly available technologies often seek a balance from a single formulation, making it difficult to simultaneously meet the requirements of cable protection pipes for external hammer impact resistance, internal thermal stability, flame retardancy, and long-term service dimensional stability.

[0005] In summary, there is an urgent need for a CPVC cable protection pipe and its preparation method, which can solve the problem of balancing heat resistance and impact resistance while maintaining a high Vicat softening temperature and flame retardancy. Summary of the Invention

[0006] This invention provides a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe and its preparation method, which adopts a multi-layer co-extrusion structure with an outer toughened layer, an inner heat-resistant reinforced layer, and a gradient transition layer for compatibility connection.

[0007] The specific technical solution is as follows: A method for preparing heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit is as follows: S1: Raw material pretreatment.

[0008] S11: The CPVC resin is dried to obtain dried CPVC resin.

[0009] S12: The nano-silica is dried, then sprayed with a silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain modified nano-silica.

[0010] S13: Dry the silicon carbide whiskers, then spray them with a silane coupling agent ethanol solution for modification, heat and stir, and cool to room temperature to obtain modified silicon carbide whiskers.

[0011] S14: The acrylate elastomer microspheres are dried, then coated with a silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain pretreated acrylate elastomer microspheres.

[0012] S2: Preparation of outer layer material: CPVC resin dried by S11, ACR modifier, and pretreated acrylate elastomer microspheres prepared by S14 are mixed and stirred at low speed. Then, polyester plasticizer, dimethyl tin oxide, and stearic acid are added and stirred at high speed. The mixture is then cooled to room temperature to obtain the outer layer compound.

[0013] S3: Inner layer material preparation: Mix half of the dried CPVC resin (S11), the modified nano-silica prepared in S12, and the modified silicon carbide whiskers prepared in S13, stir at low speed, then add the remaining dried CPVC resin, dimethyl tin oxide, and lubricant, continue stirring, then add ACR processing aid, stir at high speed, and cool to room temperature to obtain the inner layer mixture.

[0014] S4: Preparation of gradient transition layer material: The outer layer mixture prepared in S2 is mixed with the inner layer mixture prepared in S3, and then maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed and cooled to obtain the gradient transition layer mixture.

[0015] S5: Multi-layer co-extrusion, the outer layer compound prepared by S2, the inner layer compound prepared by S3, and the gradient transition layer compound prepared by S4 are added to different extruders, co-extruded and compounded, cooled in sections, drawn, and cut to obtain heat-resistant, flame-retardant and impact-resistant CPVC cable protection pipe.

[0016] Furthermore, the drying process described in S11, which reduces the moisture content to ≤0.3%, has the following parameters: temperature 80–100°C, duration 2–4 hours.

[0017] The heating and stirring described in S12 has the following parameters: temperature 100-120℃, rotation speed 800-1200rpm, and duration 15-30min.

[0018] The modified nano-silica described in S12, based on 100 parts by weight of nano-silica, contains 1 to 5 parts of silane coupling agent, wherein the silane coupling agent is KH-550.

[0019] The heating and stirring described in S13 has the following parameters: temperature 80~110℃, speed 800~1200rpm, and duration 10~20min.

[0020] The modified silicon carbide whiskers described in S13, based on 100 parts by weight of silicon carbide whiskers, contain 0.5 to 3 parts by weight of silane coupling agent, wherein the silane coupling agent is KH-550.

[0021] The drying process described in S14 has the following parameters: temperature 60-80℃, duration 2-4h.

[0022] The heating and stirring described in S14 has the following parameters: temperature 80-90℃, rotation speed 800-1200rpm, and duration 10-20min.

[0023] The pretreated acrylate elastomer microspheres described in S14, based on 100 parts by weight of acrylate elastomer microspheres, contain 0.5 to 3 parts by weight of silane coupling agent, wherein the silane coupling agent is KH-550.

[0024] Furthermore, the low-speed stirring described in S2 has the following parameter settings: rotation speed 300-500 rpm, duration 3-5 min.

[0025] The high-speed stirring described in S2 has the following parameters: temperature 80-110℃, speed 800-1200rpm, and duration 10-30min.

[0026] The outer layer compound described in S2, based on 100 parts by weight of dried CPVC resin, comprises the following other raw materials: 5-15 parts of ACR modifier, 3-10 parts of pretreated acrylate elastomer microspheres, 3-10 parts of polyester plasticizer, 2-5 parts of dimethyl tin oxide, and 1-4 parts of stearic acid.

[0027] Furthermore, the low-speed stirring described in S3 has the following parameter settings: rotation speed 300-500 rpm, duration 3-5 min.

[0028] The high-speed stirring described in S3 has the following parameters: rotation speed 800-1200 rpm, duration 15-25 min, and temperature 90-110℃.

[0029] The inner layer compound described in S3, based on 100 parts by weight of dried CPVC resin, comprises the following other raw materials: 3-12 parts of modified nano silica, 2-8 parts of modified silicon carbide whiskers, 2-5 parts of dimethyl tin oxide, 1-6 parts of ACR processing aid, and 1-4 parts of stearic acid.

[0030] Furthermore, the high-speed stirring described in S4 has the following parameter settings: rotation speed 800-1200 rpm, duration 10-20 min, and temperature 80-120℃.

[0031] The gradient transition layer compound described in S4 has an inner layer compound to outer layer compound mass ratio of (3-7):(7-3) and maleic anhydride grafted chlorinated polyolefin addition amount of 1%-5% of the total mass of inner layer compound and outer layer compound.

[0032] Furthermore, the parameters of the co-extrusion composite described in S5 are set as follows: inner layer feeding section temperature 160-170℃, compression section 175-185℃, homogenization section 180-190℃, transition layer feeding section temperature 165-175℃, compression section 180-190℃, homogenization section 185-195℃, outer layer feeding section temperature 155-165℃, compression section 170-180℃, homogenization section 175-185℃, and co-extrusion die temperature 180-200℃.

[0033] The segmented cooling described in S5 has the following parameter settings: first segment water temperature 25-30℃, second segment water temperature 20-25℃, and third segment water temperature 15-20℃.

[0034] The heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe described in S5 has a wall thickness ratio of (20-30):(10-20):(50-70) for its inner layer, transition layer, and outer layer.

[0035] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses ACR impact modifier and polyester plasticizer mainly distributed on the outer side of the pipe wall in the outer layer, which can absorb the impact energy of the drop hammer, reduce external impact cracking, and at the same time avoid the toughening components being excessively dispersed in the entire pipe wall, thus reducing the overall heat resistance.

[0036] 2. This invention improves thermal stability through silicon carbide whiskers and absorbs impact energy through surface-treated elastomer microspheres. Attached Figure Description

[0037] Figure 1 This is a process flow diagram for the preparation of a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe.

[0038] Figure 2These are microscopic morphology images of the heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes prepared in Example 1 and Comparative Examples 1-4, wherein... Figure 2 (a) is a low-magnification cross-sectional view of the topography. Figure 2 (b) is a high-magnification morphology image of the inner layer. Figure 2 (c) is a high-magnification morphology image of the outer layer. Figure 2 (d) is a topography diagram of the transition layer, H is Example 1, and C1-C4 are Comparative Examples 1-4. Detailed Implementation

[0039] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.

[0040] This invention proposes a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe and its preparation method, as shown in the appendix. Figure 1 The diagram shown is a process flow chart for the preparation of a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe. The detailed technical solution is as follows: 1. Raw material pretreatment The CPVC resin is dried to obtain dried CPVC resin.

[0041] The nano-silica was dried, then sprayed with a silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain modified nano-silica.

[0042] The silicon carbide whiskers were dried, then sprayed with a silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain modified silicon carbide whiskers.

[0043] The acrylate elastomer microspheres were dried, then coated with a silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain pretreated acrylate elastomer microspheres.

[0044] CPVC resin molecules contain polar chlorine atoms, giving them a degree of hygroscopicity. The presence of moisture can vaporize during subsequent high-temperature extrusion, leading to defects such as bubbles and silver streaks inside the pipe, affecting its mechanical properties and appearance. Furthermore, moisture at high temperatures accelerates the dehydrochlorination degradation reaction of the CPVC molecular chains, reducing the material's heat resistance and service life. Preheating and drying can control the free and bound water content in the resin to below 0.3%, ensuring the stability of subsequent processing and the quality of the finished product.

[0045] Unmodified nano-SiO2 contains a large number of silanol groups on its surface, exhibiting strong hydrophilicity and surface energy, making it prone to aggregation and difficult to disperse uniformly in the CPVC matrix. The silane coupling agent KH-550, upon hydrolysis, generates silanol, whose silanol groups can undergo dehydration condensation with the hydroxyl groups on the nano-SiO2 surface to form Si-O-Si covalent bonds, grafting organic functional groups onto the nano-SiO2 surface. After modification, the nano-SiO2 surface changes from hydrophilic to oleophilic, significantly improving its compatibility and dispersibility with the CPVC matrix.

[0046] Silicon carbide whiskers contain a small amount of active hydroxyl groups and oxide layers on their surface, resulting in weak interfacial bonding with the CPVC matrix. Direct addition can easily lead to stress concentration at the interface, reducing material performance. The silane coupling agent KH-550 contains amino functional groups. The silanol groups at one end of KH-550 can chemically bond with the hydroxyl groups on the surface of silicon carbide whiskers, while the organic functional groups at the other end can physically entangle or chemically react with the CPVC molecular chains.

[0047] The surface of elastomer microspheres is inert, resulting in poor interfacial affinity with the CPVC matrix. Untreated elastomer microspheres tend to aggregate within the CPVC matrix, exhibiting weak interfacial bonding. Upon impact, the microspheres easily detach from the matrix, failing to effectively exert their toughening effect. Through surface activation treatment with coupling agents, coupling agent molecules are adsorbed or chemically bonded to the surface of the elastomer microspheres, introducing organic functional groups with good compatibility with CPVC. The surface-treated elastomer microspheres exhibit excellent interfacial bonding with the CPVC matrix, effectively inducing crazes and shear bands upon impact, absorbing a large amount of impact energy, and significantly improving the impact resistance of the pipe.

[0048] 2. Preparation of outer layer material The dried CPVC resin, ACR modifier, and pretreated acrylate elastomer microspheres were mixed and stirred at low speed. Then, polyester plasticizer, dimethyl tin oxide, and stearic acid were added and stirred at high speed. The mixture was then cooled to room temperature to obtain the outer layer compound.

[0049] ACR impact modifier has a core of cross-linked butyl acrylate rubber and a shell of methyl methacrylate polymer with excellent compatibility with CPVC. ACR particles are uniformly dispersed within the CPVC matrix. When the material is subjected to external impact, the rubber phase core of the ACR particles can induce numerous crazing and shear bands, absorbing and dispersing impact energy. Simultaneously, the addition of ACR significantly improves the gelation degree of CPVC, promotes plasticization, and improves the processing performance of CPVC. Strong intermolecular forces exist between the ester groups on the polyester plasticizer molecular chain and the polar chlorine atoms on the CPVC molecular chain. The plasticizer molecules insert between the CPVC molecular chains, weakening the van der Waals forces and increasing the mobility of the molecular chains. This lowers the glass transition temperature and melt viscosity of CPVC, improving the material's flexibility and processing fluidity. Furthermore, the high molecular weight of polyester plasticizers results in extremely low volatility and migration, ensuring the durability of the plasticizing effect during long-term use. ACR modifiers and polyester plasticizers have a synergistic effect in CPVC: on the one hand, ACR promotes the gelation and plasticization of CPVC; on the other hand, polyester plasticizers reduce melt viscosity and improve flowability. The combined use of these two ensures excellent impact resistance of the outer layer material, good processing flowability and flexibility, while the high durability of polyester plasticizers avoids the migration defects of traditional small-molecule plasticizers.

[0050] 3. Inner layer material preparation Half of the dried CPVC resin, modified nano silica, and modified silicon carbide whiskers were mixed and stirred at low speed. Then the remaining dried CPVC resin, dimethyl tin oxide, and lubricant were added and stirred. ACR processing aid was then added and stirred at high speed. The mixture was cooled to room temperature to obtain the inner layer mixture.

[0051] Nano-SiO2 particles possess a large specific surface area and surface energy. After surface modification with a silane coupling agent, their surface changes from hydrophilic to oleophilic, significantly improving their interfacial compatibility with the CPVC matrix. Within the CPVC matrix, the uniform dispersion of nano-SiO2 particles allows numerous active groups on their surface to interact physically or chemically with the CPVC molecular chains, forming an organic-inorganic hybrid network structure. This hybrid network effectively restricts the movement of the CPVC molecular chains, shifting the glass transition temperature towards higher temperatures and significantly improving heat resistance. Simultaneously, nano-SiO2 particles act as stress concentration points, inducing crazes and shear bands in the matrix, absorbing impact energy and providing both reinforcement and toughening. When the material is subjected to external forces, the stress is transferred from the CPVC matrix to the silicon carbide whiskers through the interface. The whiskers bear most of the load, acting as a "microskeleton" reinforcement. Furthermore, when crack propagation encounters whiskers, the whiskers can prevent further crack propagation through a bridging effect; the whiskers must overcome interfacial frictional resistance when pulled out of the matrix, a process that absorbs a significant amount of energy. Therefore, the addition of silicon carbide whiskers can improve the heat resistance and strength of the material while maintaining good toughness. Modified nano-SiO2 and silicon carbide whiskers form a "nano-micro" multi-scale reinforcing network in the CPVC matrix. Nano-SiO2 fills the micro-voids between the whisker network, and the two work together to construct a denser reinforcing skeleton. Nano-SiO2 mainly improves heat resistance and strengthens the matrix, while silicon carbide whiskers mainly improve mechanical strength and impact resistance. The synergistic effect of the two makes the inner layer an excellent heat-resistant support layer.

[0052] ACR processing aid is a copolymer of methyl methacrylate and acrylate monomers, exhibiting excellent compatibility with CPVC. During high-speed mixing and subsequent extrusion processing, ACR molecular chains can intercalate between CPVC molecular chains, increasing the interchain spacing and reducing intermolecular forces, thereby promoting the plasticization and gelation of CPVC. The addition of ACR can effectively reduce the equilibrium torque of CPVC and shorten the plasticizing time.

[0053] 4. Preparation of gradient transition layer materials The outer layer compound is mixed with the inner layer compound, and then maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed and cooled to obtain the inner transition layer compound. The outer layer compound is mixed with the inner layer compound, and then maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed and cooled to obtain the outer transition layer compound.

[0054] By mixing the inner and outer layer materials in different proportions, a continuous gradient change in the pipe's cross-sectional direction is achieved. Near the inner layer, the proportion of the inner layer material is higher, with relatively higher contents of silicon carbide whiskers and nano-SiO2, resulting in excellent heat resistance. Near the outer layer, the proportion of the outer layer material is higher, with relatively higher contents of elastomer microspheres and ACR, resulting in excellent impact resistance. This gradient structure allows for a smooth transition in the pipe's cross-sectional properties from the heat-resistant, reinforced inner layer to the impact-resistant, toughened outer layer, avoiding the interfacial stress concentration and delamination failure problems caused by abrupt performance changes in traditional double-layer structures. Maleic anhydride-grafted chlorinated polyolefin tightly bonds the inner and outer layers together, effectively reducing interlayer interfacial tension.

[0055] 5. Multilayer co-extrusion The inner layer compound, outer layer compound, and gradient transition layer compound are added to different extruders for co-extrusion compounding, segmented cooling, traction, and cutting to obtain heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes.

[0056] The gradient transition layer contains a maleic anhydride-grafted chlorinated polyolefin interfacial compatibilizer. The grafting reaction of this compatibilizer requires a relatively high temperature to proceed fully. This higher temperature also helps reduce the viscosity of the transition layer melt, allowing it to match the flow rate of the inner and outer layer melts in the die runner, thus avoiding interlayer interface fluctuations caused by flow rate differences. The inner layer contains silicon carbide whiskers and nano-SiO2 inorganic fillers. Higher temperatures help reduce the melt viscosity of the CPVC matrix, resulting in more uniform dispersion of the inorganic fillers within the matrix, while ensuring sufficient plasticization of the CPVC matrix. The outer layer contains elastomer microspheres. The rubber phase core of the elastomer microspheres may soften or even degrade at high temperatures; therefore, it is necessary to appropriately lower the processing temperature to protect the integrity of its core-shell structure and ensure its full toughening effect.

[0057] CPVC is a thermoplastic material whose molecular chains are highly active at high temperatures and gradually freeze during cooling. If the cooling rate is too fast, the large temperature difference between the inner and outer layers of the pipe will lead to uneven freezing of the molecular chains, generating significant thermal shrinkage stress inside the pipe. These internal stresses may slowly release during pipe use, causing warping or even cracking. Segmented cooling allows the pipe to cool gradually from the outside in, creating a gentler temperature gradient and reducing the generation of internal stress.

[0058] Example 1 A method for preparing heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit is as follows: Table 1 Main Raw Materials ; S1: Raw material pretreatment.

[0059] S11: Dry 400g of CPVC resin (temperature 90℃, duration 3h) to obtain dried CPVC resin.

[0060] S12: 10g of nano-silica was dried (at 90℃ for 3 hours), and then a silane coupling agent ethanol solution (0.3g KH-550, mass fraction of 10%) was sprayed on it for modification. The mixture was heated and stirred (at 110℃, at 1000 rpm for 20 minutes), and then cooled to room temperature to obtain modified nano-silica.

[0061] S13: Dry 10g of silicon carbide whiskers (temperature 90℃, duration 3h), then spray with silane coupling agent ethanol solution (0.18g KH-550, mass fraction 10%) for modification treatment, heat and stir (temperature 95℃, speed 1000rpm, duration 15min), cool to room temperature to obtain modified silicon carbide whiskers.

[0062] S14: 10g of acrylate elastomer microspheres were dried (temperature 70℃, time 3h), and then sprayed with silane coupling agent ethanol solution (0.18g KH-550, mass fraction 10%) for modification treatment. The mixture was heated and stirred (temperature 85℃, speed 1000rpm, time 15min), and then cooled to room temperature to obtain pretreated acrylate elastomer microspheres.

[0063] S2: Preparation of outer layer material: 100g of dried CPVC resin after S11 treatment, 10g of ACR modifier, and 6g of pretreated acrylate elastomer microspheres prepared by S14 are mixed and stirred at low speed (400 rpm for 4 min). Then, 6.5g of polyester plasticizer, 3.5g of dimethyl tin oxide, and 2.5g of stearic acid are added and stirred at high speed (95℃, 1000 rpm for 20 min). After cooling to room temperature, the outer layer mixture is obtained.

[0064] S3: Inner layer material preparation: Half (50g) of dried CPVC resin after S11 treatment, 7.5g of modified nano-silica prepared by S12, and 5g of modified silicon carbide whiskers prepared by S13 are mixed and stirred at low speed (400rpm for 4min). Then, the remaining (50g) of dried CPVC resin, 3.5g of dimethyl tin oxide, and 2.5g of lubricant are added and stirred. Then, 3.5g of ACR processing aid is added and stirred at high speed (100℃, 1000rpm for 20min). After cooling to room temperature, the inner layer mixture is obtained.

[0065] S4: Preparation of gradient transition layer material: 14g of the outer layer mixture prepared by S2 is mixed with 6g of the inner layer mixture prepared by S3, and then 0.6g of maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed (temperature 100℃, speed 1000rpm, time 15min), cooled, and the inner transition layer mixture is obtained. 6g of the outer layer mixture prepared by S2 is mixed with 14g of the inner layer mixture prepared by S3, and then 0.6g of maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed (temperature 100℃, speed 1000rpm, time 15min), cooled, and the outer transition layer mixture is obtained.

[0066] S5: Multilayer co-extrusion. 60g of the outer layer compound prepared by S2, 25g of the inner layer compound prepared by S3, 7.5g of the inner transition layer compound prepared by S4, and 7.5g of the outer transition layer compound prepared by S4 are added to four extruders for co-extrusion and compounding. The mixture is cooled in stages (the water temperature of the first stage is 27℃, the water temperature of the second stage is 23℃, and the water temperature of the third stage is 18℃), pulled, and cut to obtain heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe (the wall thickness ratio of the inner layer, transition layer, and outer layer is 25:15:60, where the wall thickness ratio of the inner transition sub-layer and the outer transition sub-layer in the gradient transition layer is 1:1). The co-extrusion composite parameters are set as follows: inner layer feeding section temperature 165℃, compression section 180℃, homogenization section 185℃, transition layer feeding section temperature 170℃, compression section 185℃, homogenization section 190℃, outer layer feeding section temperature 160℃, compression section 175℃, homogenization section 180℃, and co-extrusion die temperature 190℃.

[0067] Example 2 The composition and preparation process are the same as in Example 1, except that: The drying parameters in step S11 of the preparation process are set as follows: temperature 80℃, duration 2h, and other steps are the same.

[0068] The temperature and stirring parameters in step S12 of the preparation process are set as follows: temperature 100℃, rotation speed 800rpm, duration 15min, and other steps are the same.

[0069] The modified nano-silica in the S12 preparation process, by weight, consists of 100 parts of nano-silica, 1 part of silane coupling agent, and other components are the same.

[0070] The heating and stirring parameters in step S13 of the preparation process are set as follows: temperature 80℃, rotation speed 800rpm, duration 10min, and other steps are the same.

[0071] The modified silicon carbide whiskers in the S13 preparation process, based on 100 parts by weight of silicon carbide whiskers, contain 0.5 parts of silane coupling agent, with other components being the same.

[0072] In the preparation process S14, the drying parameters are set as follows: temperature 60℃, duration 2h; the heating and stirring parameters are set as follows: temperature 80℃, speed 800rpm, duration 10min; and other steps are the same.

[0073] In the preparation process S14, the pretreated acrylate elastomer microspheres are based on 100 parts by weight of acrylate elastomer microspheres, with 0.5 parts of silane coupling agent and other components being the same.

[0074] The S2 stirring parameters for the preparation process are set as follows: low speed stirring speed 300 rpm, duration 3 min; high speed stirring parameters are set as follows: temperature 80℃, speed 800 rpm, duration 10 min; other steps are the same.

[0075] The outer layer compound in the S2 preparation process, based on 100 parts by weight of dried CPVC resin, consists of the following raw materials: 5 parts ACR modifier, 3 parts pretreated acrylate elastomer microspheres, 3 parts polyester plasticizer, 2 parts dimethyl tin oxide, 1 part stearic acid, and the other components are the same.

[0076] Example 3 The composition and preparation process are the same as in Example 1, except that: The drying parameters in step S11 of the preparation process are set as follows: temperature 100℃, duration 4h, and other steps are the same.

[0077] The heating and stirring parameters in step S12 of the preparation process are set as follows: temperature 120℃, rotation speed 1200rpm, duration 30min, and other steps are the same.

[0078] The modified nano-silica in the S12 preparation process, based on 100 parts by weight of nano-silica, contains 5 parts of silane coupling agent, with other components being the same.

[0079] The heating and stirring parameters in step S13 of the preparation process are set as follows: temperature 110℃, rotation speed 1200rpm, duration 20min, and other steps are the same.

[0080] In the preparation process S13, the modified silicon carbide whiskers, based on 100 parts by weight of silicon carbide whiskers, contain 3 parts of silane coupling agent, and the other components are the same.

[0081] In the preparation process S14, the drying parameters are set as follows: temperature 80℃, duration 4h; the heating and stirring parameters are set as follows: temperature 90℃, speed 1200rpm, duration 20min; and other steps are the same.

[0082] In the preparation process S14, the pretreated acrylate elastomer microspheres are based on 100 parts by weight of acrylate elastomer microspheres, with 3 parts of silane coupling agent and other components being the same.

[0083] The S2 stirring parameters for the preparation process are set as follows: low speed stirring speed 500 rpm, time 5 min; high speed stirring parameters are set as follows: temperature 110℃, speed 1200 rpm, time 30 min; other steps are the same.

[0084] The outer layer compound in the S2 preparation process, based on 100 parts by weight of dried CPVC resin, has the following composition of other raw materials: 15 parts ACR modifier, 10 parts pretreated acrylate elastomer microspheres, 10 parts polyester plasticizer, 5 parts dimethyl tin oxide, 4 parts stearic acid, and the other components are the same.

[0085] Example 4 The composition and preparation process are the same as in Example 1, except that: The S3 stirring parameters for the preparation process are set as follows: low speed stirring speed 300 rpm, duration 3 min; high speed stirring parameters are set as follows: 800 rpm, duration 15 min, temperature 90℃. Other steps are the same.

[0086] The inner layer mixture in the S3 preparation process, based on 100 parts by weight of dried CPVC resin, consists of the following raw materials: 3 parts modified nano silica, 2 parts modified silicon carbide whiskers, 2 parts dimethyl tin oxide, 1 part ACR processing aid, 1 part stearic acid, and the other components are the same.

[0087] In the S4 step of the preparation process, the high-speed stirring parameters are set as follows: rotation speed 800 rpm, duration 10 min, temperature 80℃, and other steps are the same.

[0088] Example 5 The composition and preparation process are the same as in Example 1, except that: The S3 stirring parameters for the preparation process are set as follows: low speed stirring speed 500 rpm, duration 5 min; high speed stirring parameters are set as follows: speed 1200 rpm, duration 25 min, temperature 110℃. Other steps are the same.

[0089] The inner layer mixture in the S3 preparation process, based on 100 parts by weight of dried CPVC resin, consists of the following raw materials: 12 parts modified nano silica, 8 parts modified silicon carbide whiskers, 5 parts dimethyl tin oxide, 6 parts ACR processing aid, and 4 parts stearic acid, with the other components being the same.

[0090] The high-speed stirring parameters in step S4 of the preparation process are set as follows: rotation speed 1200 rpm, duration 20 min, temperature 120℃, and other steps are the same.

[0091] Example 6 The composition and preparation process are the same as in Example 1, except that: In the S4 step of the preparation process, the high-speed stirring parameters are set as follows: rotation speed 800 rpm, duration 10 min, temperature 80℃, and other steps are the same.

[0092] In process S4, the mass ratio of the inner layer mixture to the outer layer mixture in the inner transition layer mixture is 5:5, and the amount of maleic anhydride-grafted chlorinated polyolefin added is 1% of the total mass of the inner and outer layer mixtures. In the outer transition layer mixture, the mass ratio of the inner layer mixture to the outer layer mixture is 5:5, and the amount of maleic anhydride-grafted chlorinated polyolefin added is 1% of the total mass of the inner and outer layer mixtures. Other components are the same.

[0093] The S5 co-extrusion composite parameters for the preparation process are set as follows: inner layer feeding section temperature 160℃, compression section 175℃, homogenization section 180℃, transition layer feeding section temperature 165℃, compression section 180℃, homogenization section 185℃, outer layer feeding section temperature 155℃, compression section 170℃, homogenization section 175℃, co-extrusion die temperature 180℃. The segmented cooling parameters are set as follows: first segment water temperature 25℃, second segment water temperature 20℃, third segment water temperature 15℃, and other steps are the same.

[0094] In the S5 preparation process, the wall thickness ratio of the inner layer, transition layer and outer layer is 20:10:70, and the other components are the same.

[0095] Example 7 The composition and preparation process are the same as in Example 1, except that: The high-speed stirring parameters in step S4 of the preparation process are set as follows: rotation speed 1200 rpm, duration 20 min, temperature 120℃, and other steps are the same.

[0096] In process S4, the mass ratio of the inner layer mixture to the outer layer mixture in the inner transition layer mixture is 3:7, and the amount of maleic anhydride-grafted chlorinated polyolefin added is 5% of the total mass of the inner and outer layer mixtures. In the outer transition layer mixture, the mass ratio of the inner layer mixture to the outer layer mixture is 7:3, and the amount of maleic anhydride-grafted chlorinated polyolefin added is 5% of the total mass of the inner and outer layer mixtures. Other components are the same.

[0097] The S5 co-extrusion composite parameters for the preparation process are set as follows: inner layer feeding section temperature 170℃, compression section 185℃, homogenization section 190℃, transition layer feeding section temperature 175℃, compression section 190℃, homogenization section 195℃, outer layer feeding section temperature 165℃, compression section 180℃, homogenization section 185℃, co-extrusion die temperature 200℃. The segmented cooling parameters are set as follows: first segment water temperature 30℃, second segment water temperature 25℃, third segment water temperature 20℃, and other steps are the same.

[0098] In the S5 preparation process, the wall thickness ratio of the inner layer, transition layer and outer layer is 30:20:50, and the other components are the same.

[0099] Comparative Example 1 The composition and preparation process are the same as in Example 1, except that: In step S2 of the preparation process, no pretreated acrylate elastomer microspheres are added; the other steps are the same.

[0100] Comparative Example 2 The composition and preparation process are the same as in Example 1, except that: In step S3 of the preparation process, no modified silicon carbide whiskers are added; the other steps are the same.

[0101] Comparative Example 3 The composition and preparation process are the same as in Example 1, except that: In step S4 of the preparation process, maleic anhydride-grafted chlorinated polyolefin is not added, while the other steps are the same.

[0102] Comparative Example 4 The composition and preparation process are the same as in Example 1, except that: In the preparation process, the gradient transition layer preparation in S4 is removed. In S5, a two-layer co-extrusion extruder is used for forming, and the outer layer and inner layer are directly compounded without a transition layer. The other steps are the same.

[0103] Samples were taken from the heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes prepared in Example 1 and Comparative Examples 1-4. Arc-shaped pipe sections (10mm long, 10mm wide) were cut axially. The radial sections of the pipe wall were embedded into cold-mounted epoxy resin with the pipe wall facing upwards. The mixture was cured at room temperature for 10 hours, then sanded, polished, washed, dried, and sputter-coated with gold. Morphology tests were then performed. Figure 2 As shown, where, Figure 2 (a) is a low-magnification cross-sectional view of the topography. Figure 2 (b) is a high-magnification morphology image of the inner layer. Figure 2 (c) is a high-magnification morphology image of the outer layer. Figure 2 (d) is a topographic diagram of the transition layer, H is Example 1, and C1-C4 are comparative examples 1-4. Figure 2 In (a), the low-magnification radial section of H shows the inner surface, inner layer, transition layer, outer layer, and outer surface. The interlayer contours are continuous, and the macroscopic layered structure of C1, C2, and C3 is still present. However, C3 shows fine dark lines, micropores, or localized delamination at the interface, while C4 shows cracks, delamination, or abrupt changes in grayscale near the interface. Figure 2In (b), the modified silicon carbide crystals in H are dispersed in the matrix as short rods, needles, or fibers; the modified nano-SiO2 is distributed as fine particles or locally dense bright spots; the inner layer of C1 still contains whiskers and particles; the inner layer of C2 lacks needle / rod-like reinforcing phases; the microskeleton and bridging features are insufficient; C3 shows local microcracks in the region near the transition layer; the inner layer of C4 still contains whiskers, but the stress concentration is more obvious near the direct composite interface; Figure 2 In (c), the outer layer of H has a large number of near-spherical elastomer microspheres uniformly embedded in the CPVC matrix. The diameter of the microspheres is mainly in the hundreds of nanometers. Locally, microsphere-induced crazes, shear bands, microporosity, or rough plastic fracture morphology are visible. C1 lacks regular spherical dispersed phases, and the fracture surface is straighter with fewer dimples and plastic stretching traces. Elastomer microspheres can still be observed in C2; however, due to the lack of whisker support in the inner layer, the overall tube is not adequately supported under thermal / mechanical coupling. The outer layer of C3 may contain microspheres, but the interface connection area lacks compatibilizer, making local delamination more likely between the outer layer and the transition layer. The outer layer of C4 may still contain microspheres, but the outer layer is in direct contact with the inner layer, and impact cracks may propagate along the abrupt interface. Figure 2 In (d), the inner / transition layer and the transition layer / outer layer interfaces of H are continuously connected. More whiskers / inorganic phases are seen near the inner layer, while more spherical elastic phases or ductile fracture traces are seen near the outer layer. Micropores, local debonding, and cracks extending along the interlayer are observed at the C3 interface. More obvious interface abrupt changes, continuous dark cracks, or cracks deflected to the interface and rapidly propagating are seen at C4, indicating that stress concentration exists in the traditional double-layer structure.

[0104] Based on Examples 1-7 and Comparative Examples 1-4, samples of the finally prepared heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes were taken and subjected to Vicat softening temperature tests: An arc-shaped pipe section (50 mm long, 10 mm wide, and 4 mm thick) was cut along the axial direction of the sample, then treated at 50°C for 5 minutes, and then placed in an environment of 23°C and 50% relative humidity for 48 hours, with the concave side facing upwards, so that the cross-sectional area is 1 mm². 2 The flat-headed indenter is perpendicularly contacted with the sample surface, and a load of 50N is applied. Glycerin is used as the heat transfer medium, and the temperature is increased (50℃ / h). When the depth of the indenter into the sample surface reaches (1±0.01)mm, the temperature at this time is recorded. This temperature is the Vicat softening temperature of the sample. Three sets of measurements are taken, and the average value is taken. If the test results of any two samples differ by more than 2℃, at least two samples are retested.

[0105] Based on Examples 1-7 and Comparative Examples 1-4, samples of the finally prepared heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe were taken for notched impact strength testing: an arc-shaped pipe section (80mm long, 10mm wide, and 4mm thick) was cut along the axial direction of the sample, a V-shaped notch was machined, and the sample was placed in an environment of 23℃ and 50% relative humidity for 48 hours. The sample was then placed horizontally on the two support blocks of the testing machine, the pendulum was released, the impact energy absorbed by the sample during fracture was recorded, the remaining width at the notch of the sample was measured, and the results were calculated. Five sets of measurements were taken, and the average value was taken.

[0106] Based on Examples 1-7 and Comparative Examples 1-4, samples of the finally prepared heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes were taken for oxygen index testing: an arc-shaped pipe section (80mm long, 10mm wide, and 4mm thick) was cut along the axial direction of the sample. A mark was drawn on the sample 50mm from the ignition end. The sample was placed in an environment of 23℃ and 50% relative humidity for 96 hours. The oxygen index was tested using an oxygen index meter. Nitrogen gas was turned on first, followed by oxygen gas. The mixed gas flow was allowed to flow in the combustion chamber for 30 seconds. Then, the top of the sample was ignited with an igniter. The igniter was removed immediately after ignition, and the timer was started. If the flame continued to burn for 180 seconds or the flame front burned past the 50mm mark on the sample, it was recorded as "burning". Otherwise, it was recorded as "extinguished". The oxygen concentration of the next sample was adjusted according to the result of the previous sample, with a gradient of 0.5%.

[0107] Based on Examples 1-7 and Comparative Examples 1-4, samples of the finally prepared heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe were taken and subjected to tensile strength tests: the cut pipe sections were processed into dumbbell-shaped specimens and placed in an environment of 23°C and 50% relative humidity for 96 hours. The test was conducted using a universal testing machine (tensile speed 5 mm / min). The maximum force that the specimen could withstand before fracture was recorded, and the width of the fracture point of the specimen was measured and recorded. The values ​​of 5 sets of measurements were calculated and averaged.

[0108] Based on Examples 1-7 and Comparative Examples 1-4, samples of the finally prepared heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipes were taken for interlayer peel strength testing: an arc-shaped pipe section (120 mm long and 15 mm wide) was cut along the axial direction of the sample and placed in an environment of 23°C and 50% relative humidity for 48 hours. The test was conducted using a universal testing machine (peeling speed 50 mm / min, peeling angle 90°). The average force of the stable peeled section was recorded, and 5 sets of measurements were taken, with the average value taken.

[0109] The specific test results are shown in Table 2. Figure 2 As shown: Table 2 Comparison of core performance of Examples 1-7 and Comparative Examples 1-4 ; The comparison results above show that Example 1 has the best overall performance. The ACR modifier and pretreated acrylate elastomer microspheres synergistically toughen the material, while modified nano-silica and modified silicon carbide whiskers act as rigid reinforcing fillers, improving overall heat resistance. The outer and inner layer mixtures are mixed in a 1:1 ratio, and maleic anhydride-grafted chlorinated polyolefin is added to achieve a smooth performance transition, avoiding heat resistance loss caused by abrupt changes in interlayer performance. This demonstrates that Example 1 successfully solves the contradiction between heat resistance and impact resistance in current CPVC cable protection pipes. Examples 2 to 7 show better overall performance. Slightly lower than Example 1 but still at a high level, indicating that excellent performance balance was achieved despite a wide range of parameter variations. Comparative Example 1, lacking pretreated acrylate elastomer microspheres, relied solely on ACR modifier for insufficient toughening, resulting in lower strength. Comparative Example 2, without modified silicon carbide whiskers, lacked rigid reinforcing fillers, resulting in insufficient heat-resistant support in the inner layer and a decrease in overall heat resistance. Comparative Example 3, without maleic anhydride-grafted chlorinated polyolefin, exhibited poor interlayer interface compatibility. Comparative Example 4 lacked a gradient transition layer, with direct composite between the outer and inner layers, leading to interface stress concentration and a tendency for delamination and cracking.

[0110] In summary, it can be clearly seen from the above embodiments and comparative examples that the heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe provided by the present invention has a significant improvement in the balance between heat resistance and impact resistance. This is attributed to the construction of a three-layer gradient structure design, consisting of an outer layer of elastomer toughening, an inner layer of rigid filler reinforcement, and a gradient transition layer for compatibility, thereby solving the contradiction between heat resistance and impact resistance in the heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe.

Claims

1. A heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit, characterized in that: The pipe has a three-layer composite structure, consisting of an inner layer, a gradient transition layer, and an outer layer from the inside out. The inner layer, by weight, comprises the following raw materials: based on 100 parts of dried CPVC resin, 3-12 parts of modified nano-silica, 2-8 parts of modified silicon carbide whiskers, 2-5 parts of dimethyl tin oxide, 1-6 parts of ACR processing aid, and 1-4 parts of stearic acid. The outer layer, by weight, comprises the following raw materials: based on 100 parts of dried CPVC resin, 3-12 parts of modified nano-silica, 2-8 parts of modified silicon carbide whiskers, 2-5 parts of dimethyl tin oxide, 1-6 parts of ACR processing aid, and 1-4 parts of stearic acid. Based on dried CPVC resin, 5-15 parts of ACR modifier, 3-10 parts of pretreated acrylate elastomer microspheres, 3-10 parts of polyester plasticizer, 2-5 parts of dimethyl tin oxide, and 1-4 parts of stearic acid are added; the gradient transition layer is formed by mixing the inner layer compound and the outer layer compound in a mass ratio of (3-7):(7-3), with a total of 100 parts of the inner layer compound and the outer layer compound as the basis, and an additional 1-5 parts of maleic anhydride grafted chlorinated polyolefin are added.

2. The heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit according to claim 1, characterized in that: The modified nano-silica, by weight, comprises 1 to 5 parts of silane coupling agent based on 100 parts of nano-silica, wherein the silane coupling agent is KH-550.

3. The heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit according to claim 1, characterized in that: The modified silicon carbide whiskers, by weight, consist of 0.5 to 3 parts of silane coupling agent per 100 parts of silicon carbide whiskers, wherein the silane coupling agent is KH-550.

4. The heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit according to claim 1, characterized in that: The pretreated acrylate elastomer microspheres, by weight, consist of 0.5 to 3 parts of silane coupling agent, with 100 parts of acrylate elastomer microspheres as a basis. The silane coupling agent is KH-550.

5. The heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit according to claim 1, characterized in that, The heat-resistant, flame-retardant and impact-resistant CPVC cable protection pipe has a wall thickness ratio of (20-30):(10-20):(50-70) for its inner layer, gradient transition layer and outer layer.

6. A method for preparing a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection conduit according to any one of claims 1-5, characterized in that, Includes the following steps: S1: Raw material pretreatment; S11: The CPVC resin is dried to obtain dried CPVC resin; S12: The nano-silica is dried, then sprayed with silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain modified nano-silica. S13: Dry the silicon carbide whiskers, then spray them with a silane coupling agent ethanol solution for modification, heat and stir, cool to room temperature to obtain modified silicon carbide whiskers. S14: The acrylate elastomer microspheres are dried, then sprayed with silane coupling agent ethanol solution for modification, heated and stirred, and cooled to room temperature to obtain pretreated acrylate elastomer microspheres. S2: Preparation of outer layer material: CPVC resin dried by S11, ACR modifier, and pretreated acrylate elastomer microspheres prepared by S14 are mixed and stirred at low speed. Then polyester plasticizer, dimethyl tin oxide, and stearic acid are added and stirred at high speed. The mixture is cooled to room temperature to obtain the outer layer compound. S3: Inner layer material preparation: Mix half of the dried CPVC resin from S11, the modified nano-silica prepared from S12, and the modified silicon carbide whiskers prepared from S13, stir at low speed, then add the remaining dried CPVC resin, dimethyl tin oxide, and lubricant, continue stirring, then add ACR processing aid, stir at high speed, and cool to room temperature to obtain the inner layer mixture. S4: Preparation of gradient transition layer material: The outer layer mixture prepared in S2 is mixed with the inner layer mixture prepared in S3, and then maleic anhydride-grafted chlorinated polyolefin is added. The mixture is stirred at high speed and cooled to obtain the gradient transition layer mixture. S5: Multi-layer co-extrusion, the outer layer compound prepared by S2, the inner layer compound prepared by S3, and the gradient transition layer compound prepared by S4 are added to different extruders, co-extruded and compounded, cooled in sections, drawn, and cut to obtain heat-resistant, flame-retardant and impact-resistant CPVC cable protection pipe.

7. The method for preparing a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe according to claim 6, characterized in that: The drying process described in S11, which reduces the moisture content to ≤0.3%, has the following parameters: temperature 80~100℃, duration 2~4h; The heating and stirring described in S12 has the following parameters: temperature 100-120℃, rotation speed 800-1200rpm, and duration 15-30min. The heating and stirring described in S13 has the following parameters: temperature 80-110℃, rotation speed 800-1200rpm, and duration 10-20min. The drying process described in S14 has the following parameter settings: temperature 60-80℃, duration 2-4h; The heating and stirring described in S14 has the following parameters: temperature 80-90℃, rotation speed 800-1200rpm, and duration 10-20min.

8. The method for preparing a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe according to claim 6, characterized in that: The low-speed stirring described in S2 has the following parameters: rotation speed 300-500 rpm, duration 3-5 min; The high-speed stirring described in S2 has the following parameters: rotation speed 800-1200 rpm, duration 10-30 min, and temperature 80-110℃. The low-speed stirring described in S3 has the following parameters: rotation speed 300-500 rpm, duration 3-5 min; The high-speed stirring described in S3 has the following parameters: rotation speed 800-1200 rpm, duration 15-25 min, and temperature 90-110℃.

9. The method for preparing a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe according to claim 6, characterized in that: The high-speed stirring described in S4 has the following parameters: rotation speed 800-1200 rpm, duration 10-20 min, and temperature 80-120℃.

10. The method for preparing a heat-resistant, flame-retardant, and impact-resistant CPVC cable protection pipe according to claim 6, characterized in that: The co-extrusion composite described in S5 has the following parameter settings: inner layer feeding section temperature 160-170℃, compression section 175-185℃, homogenization section 180-190℃, transition layer feeding section temperature 165-175℃, compression section 180-190℃, homogenization section 185-195℃, outer layer feeding section temperature 155-165℃, compression section 170-180℃, homogenization section 175-185℃, and co-extrusion die temperature 180-200℃. The segmented cooling described in S5 has the following parameter settings: first segment water temperature 25-30℃, second segment water temperature 20-25℃, and third segment water temperature 15-20℃.

Citation Information

Patent Citations

  • Chlorinated polyvinyl chloride pipeline

    CN103012998A